Sustainable and equivalent improvements in symptoms and functional well‐being following viral cure from ledipasvir/sofosbuvir versus elbasvir/grazoprevir for chronic hepatitis C infection: Findings from the randomized PRIORITIZE trial. Issue 9 (15th June 2022) - Evon, Donna M.; Dong, Meichen; Reeve, Bryce B.; Peter, Joy; Michael, Larry; Lok, Anna S.; Nelson, David R.; Stewart, Paul W.
Abstract: The PRIORITIZE trial (clinicaltrials.gov : NCT02786537) was the first comparative effectiveness study to directly compare ledipasvir/sofosbuvir (LDV/SOF) and elbasvir/grazoprevir (EBR/GZR) for the treatment of chronic hepatitis C virus (HCV). A secondary aim of this study was to compare LDV/SOF and EBR/GZR on sustainable changes in several HCV‐associated symptoms and functional well‐being in patients who achieved sustained virological response (SVR). PRIORITIZE, a randomized controlled trial conducted between 2016 and 2020, evaluated change in six PROMIS® symptom scores (fatigue, sleep disturbance, cognitive disturbance, nausea, diarrhoea, abdominal pain) and functional well‐being using the disease‐specific HCV‐PRO instrument. Survey assessments were administered at baseline, early post‐treatment (median = 6 months) and late post‐treatment (median = 21 months). Constrained longitudinal linear mixed‐effects models were used to evaluate within‐treatment change and between‐treatment differences. Data from 793 participants (average 55 years old, 57% male, 44% black, 17% with cirrhosis) were analysed. From baseline to early post‐treatment, 5 out of 6 symptoms and functional well‐being significantly improved (all p 's < .05). In the LDV/SOF arm, mean changes ranged from −3.73 for nausea to −6.41 for fatigue and in the EBR/GZR, mean changes ranged from −2.19 for cognitive impairment to −4.67 for fatigue. Change of >3 points was consider clinically meaningful. Improvements in most symptoms slightly favoured LDV/SOF, although the magnitude of differences between the regimens were small. Both regimens demonstrated significant improvements in symptoms and functional well‐being that were sustained during the late post‐treatment phase. EBR/GZR and LDV/SOF regimens had clinically equivalent and durable improvements in HCV symptoms and functional well‐being up to two years after SVR.